Alternative Mortgage Instruments, the Tilt Problem, and Consumer Welfare - Alm, James; Follain, James R. (Journal of Financial and Quantitative Analysis, 1984)
The Standard Fixed Payment Mortgage (SFPM) has been the dominant mortgage instrument in the United States for the last 50 years, and for much of this period it has performed well. However, during periods of high and volatile rates of inflation, the SFPM suffers from severe weaknesses. Foremost among these problems, from the standpoint of the borrower, is the tilt in the stream of real mortgage payments toward the initial years of the mortgage. For consumers unconstrained by capital market imperfections, this tilt is unimportant. However, a consumer is typically unable to borrow against expected higher future income, or against the nominal capital gains that accrue to the owner of a house over the life of the mortgage. In addition, common practices of mortgage lenders often limit mortgage payments to some fraction of income at the time of purchase. Together, these liquidity constraints create a mismatch between the time sequence of mortgage payments and income, a mismatch that reduces the number of borrowers who qualify for financing and that limits the value of the house purchased by those who do obtain financing.